PROJECTION OF THE ESTABLISHMENT OF THE OPERATIONAL CONTROL SYSTEM - Матюха, Микола (SWorldJournal, 2023)
The work considers the system of establishing the operational controlling system, as an element of the information base for making managerial decisions.The role of the operational controlling system along with subsets of controlling - budgeting (financi